177Lu-labeled carbon nanospheres: a new entry in the field of targeted radionanomedicine. Issue 56 (24th May 2016) - Satpati, Drishty; Satpati, Ashis; Pamale, Yugandhara; Kumar, Chandan; Sharma, Rohit; Sarma, Haladhar Deb; Banerjee, Sharmila
Abstract : 177 Lu-labeled carbon nanospheres loaded with cRGDfK peptide have been developed as radionanoprobes with favorable pharmacokinetics for integrin αv β3 -mediated active targeting. Abstract : Multi-functional nanomaterial conjugates constructed with targeting ligands and therapeutic radioisotopes are key for the future clinical translation of radionanomedicine. However, the choice of the nanomaterial governs the in vivo oncological applications. In this study, recently introduced non-toxic, spherical (<50 nm) carbon nanospheres (CNS) have been modified at the surface for conjugation with integrin αv β3 -targeting peptide cRGDfK and macrocyclic chelator (DOTA). Herein we have investigated the potential of 177 Lu-labeled carbon nanospheres ( 177 Lu-DOTA-CNS–cRGDfK) for efficient nano-targeting of melanoma tumors expressing integrin αv β3 . To ascertain the specificity of 177 Lu-DOTA-CNS–cRGDfK in vivo, blocking studies with cold cRGDfK peptide as well as control experiments with radiolabeled nanoconjugate without the peptide ( 177 Lu-DOTA-CNS) were carried out. Significantly high tumor uptake of 177 Lu-DOTA-CNS–cRGDfK in comparison to that of 177 Lu-DOTA-CNS, fast urinary excretion and low uptake in the reticuloendothelial system (RES) establish the promising potential of the agent and indicate the future role of radiolabeled carbon nanospheres in radionanomedicine for efficient targeted therapy of numerous tumor sites.